ANALISIS NARASI TOLERANSI BERAGAMA DALAM FILM 99 CAHAYA DI LANGIT EROPA - Yohandi Yohandi (LP2M Universitas Ibrahimy, 2018)
99 Cahaya di Langit Eropa is one of the most inspiring movies, especially in understanding and interpreting the importance of maintaining unity in diversity. This movie teaches us about the importance of tolerance for survival in the present and future. This is important so that peoples can interpret and take lessons and moral messages from this film. This research was conducted using Todorov's narrative analysis method with the paradigm of constructivism and philosophical approach. The subject of this study is movie of 99 Cahaya di Langit Eropa, while the object of this research is religious tolerance. The technique of collecting data is with Archival Records techniques from data sources in the form of movie of 99 Cahaya di Langit Eropa.The results of this study can be concluded that in analyzing the contents of the narrative in the movie of 99 Cahaya di Langit Eropa with Tzvetan Todorov's model divided into three parts: 1) Initial Flow, 2) Middle Flow, 3) Final Flow and also four values ​​of religious tolerance displayed by the characters, namely: 1) Recognizing the Rights of Everyone, 2) Respecting the Beliefs of Others, 3) Agree in Disagreement, and 4) Understanding each other. So this movie can be a medium in preaching with the meaning of religious tolerance.